Development of Next-generation Compression Apparel. (2015) - Belbasis, Aaron; Fuss, Franz Konstantin
Abstract: Enjoyment and participation in physical activity is often hindered by fear of injury. In particular, the muscles and joints in the lower limbs suffer from a higher likelihood of injuries due to muscle and ligament overloading/straining. High-end compression gear is currently limited only to providing passive muscular and vascular exercise response. Smart Apparel introduces the integration of a pressure mapping system into a compression garment, further extending its functional support in a range of applications, from an indispensable training aid within competitive sports through to the health industry. The purpose of this research was to investigate the design considerations and developmental steps necessary in developing such a 'Smart Garment' for monitoring muscle and limb activity. It investigates the use of a novel approach to quantifying muscular exertion and loading through the measurement of surface pressures between a target muscular group and a compressive elastic garment. Surface pressure information about muscle loading is detected for both running and cycling, where the repeatable and quantifiable nature of the data aids in the modification of behaviours that predispose athletes to injury; thereby minimising injury risk, reducing recovery times, and maximising training potential.